Type-I interferon pathway and DNA damage accumulation in peripheral blood of patients with psoriatic arthritis - Fragoulis, George E.; Ntouros, Panagiotis A.; Nezos, Adrianos; Vlachogiannis, Nikolaos I.; McInnes, Iain B.; Tektonidou, Maria G.; Skarlis, Charalampos; Souliotis, Vassilis L.; Mavragani, Clio P.; Sfikakis, Petros P. (Frontiers in Immunology, 2023)
Objectives The abnormal DNA damage response is associated with upregulation of the type-1 interferon (IFN-I) pathway in certain rheumatic diseases. We investigated whether such aberrant mechanisms operate in psoriatic arthritis (PsA). Methods DNA damage levels were measured by alkaline comet assay in peripheral blood mononuclear cells from 52 PsA patients and age-sex-matched healthy individuals. RNA expression of IFIT1, MX1 and IFI44, which are selectively induced by IFN-I, was quantitated by real-time polymerase chain reaction and their composite normalized expression resulted in IFN-I score calculation. RNA expression of IL1β, IL6, TNF, IL17A and IL23A was also assessed in PsA and control subgroups. Results In PsA, DNA damage accumulation was increased by almost two-fold compared to healthy individuals (olive tail moment arbitrary units, mean ± SD; 9.42 ± 2.71 vs 4.88 ± 1.98, p<0.0001). DNA damage levels significantly correlated with serum C-Reactive-protein and IL6 RNA expression in PBMCs. Despite increased DNA damage, the IFN-I score was strikingly lower in PsA patients compared to controls (-0.49 ± 6.99 vs 4.24 ± 4.26; p<0.0001). No correlation was found between IFN-I pathway downregulation and DNA damage. However, the IFN-I score in a PsA subgroup was lower in those patients with higher IL1β expression, as well as in those with higher TNF/IL23A PBMCs expression. Conclusion DNA damage in PsA correlates with measures of inflammation but is not associated with the IFN-I pathway induction. The unexpected IFN-I downregulation, albeit reminiscent to findings in experimental models of spondyloarthritis, may be implicated in PsA pathogenesis and explained by operation of other cytokines.